Chemical and Sensory Comparison of Classical and Alternative Systems for the Ageing of Wine Distillate - Tchabashvili, Sopio; Abzianidze, Davit (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
The chemical components were quantified in artificially aged (with oak chips) and barrel-aged wine distillate. These components belong to various chemical families, including aldehydes (acetaldehyde, propionic aldehyde, furfural, coniferaldehyde, synapaldehyde), higher alcohols (methanol, ethanol, 1-Propanol, butanol, isobutanol, amyl alcohol, isoamyl alcohol, 1-hexanol), volatile acids (ethanoic acid, propionic acid, 3-methylbutanoic acid, hexanoic acid, heptanoic acid, octanoic acid) and esters (methyl formate, ethyl acetate, butyl butyrate, methyl butyrate). Chemical analysis was performed by classical methods of analytical chemistry. During the seven month aging process all the chemical components were affected by ageing systems. The analysis of alcoholic strength by volume, aldehydes and volatile acids showed a great discrimination of the brandies based on the ageing system. The loss of alcohol was lower in a glass vessel with oak chips than in oak wood barrel. Thus, artificial ageing is cost-efficient method than the classical one. Moreover, the ageing system affected the sensory profile of the wine distillates as well. The present study demonstrated that alternative ageing up to five months is the most promising technology to get desirable colour. However, traditional wine spirit ageing method is preferable to produce high quality brandy compared to alternatives as spirit aged in Limousin oak barrels are more matured than the one aged with oak chips.